State of vaccine confidence in the European Union in 2018. (13th November 2019) - Larson, H; de Figueiredo, A; Karafllakis, E; Rawal, M
Abstract: Background: High confidence in vaccination programmes is crucial for maintaining high coverage rates. Across the European Union (EU), however, vaccine delays and refusals are contributing to declining immunisation rates in a number of countries and are leading to increases in disease outbreaks. Methods: We assessed the overall state of confidence in vaccines among the public in all 28 EU member states and among general practitioners (GP) in ten EU member states, conducting the largest ever study on attitudes to vaccines and vaccination in the EU, eliciting the views of approximately 28, 000 respondents across the 28 EU member states. Results: We found that a number of member states (including France, Greece, Italy, and Slovenia) have become more confident in the safety of vaccines since 2015, but that the Czech Republic, Finland, Poland, and Sweden have become less confident. While GPs generally hold higher levels of vaccine confidence than the public, the survey found that 36% of GPs surveyed in Czech Republic and 25% in Slovakia do not agree that the MMR vaccine is safe and 29% and 19% respectively do not believe it is important. Countries whose GPs hold higher confidence in vaccines tend to have a larger proportion of the public expressing positive vaccination beliefs. Conclusions: Even countries with well-established vaccination programmes and high levels of confidence are not immune to rising vaccine hesitancy. There is a need for continuous monitoring, preparedness and response plans to maintain and increase confidence in the importance, effectiveness and safety of vaccines, among both the public and health professionals.